Mitos Politik Aliran dan Aspirasi Politik ICMI Modernis - Mujani, Saiful (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
This article is a review of the writings of Adam Schwarz, titled Islam: Coming in from the Cold in his book, A Nation in Waiting, Indonesia in the 1990's. Adam Schwarz is a reporter Far Eastern Economic Review magazine published in Hong Kong. This book is the result of observations during which he served in Indonesia in the late 80s and early 90s, a period characterized much debate about Islam in Indonesia.Started writing this, Schwarz explained about the relationship Abdurrahman Wahid (Gus Dur) with the government. A few weeks after Gus Dur Tabligh Akbar held in Senayan East Parking Lot, he was